Childhood family structure and women's adult overweight risk: A longitudinal study. Issue 5 (July 2017) - Chaparro, M. Pia; de Luna, Xavier; Häggström, Jenny; Ivarsson, Anneli; Lindgren, Urban; Nilsson, Karina; Koupil, Ilona
Aim: The aim of this study was to investigate whether women's adult overweight and obesity risk was associated with their childhood family structure, measured as their mothers' marital status history, during the women's first 18 years of life. Methods: Using linked register data, we analyzed 30, 584 primiparous women born in Sweden in 1975 who were between 19–35 years of age when their height and pre-pregnancy weight was recorded. The outcomes were women's overweight/obesity (body mass index (BMI) ≥ 25 kg/m 2 ) and obesity (BMI ≥ 30 kg/m 2 ) and the predictor was mothers' marital status history, which was summarized using sequence analysis. We carried out nested logistic regression models adjusting for women's age and maternal sociodemographic characteristics. Results: Mothers' marital status history was summarized into six clusters: stable marriage, stable cohabitation, married then divorcing, cohabiting then separating, varied transitions, and not with father. In fully adjusted models and compared with women whose mothers belonged to the stable marriage cluster: (1) women whose mothers belonged to the other marital status clusters had higher odds of overweight/obesity (odds ratio (OR) ranging 1.15–1.19; p < 0.05); and (2) women whose mothers belonged to the stable cohabitation (OR = 1.31; 95% confidence interval (CI) = 1.14–1.52), cohabiting then separating (OR = 1.23; 95% CI = 1.01–1.49), varied transitions (OR = 1.24; 95% CI = 1.11–1.39), and not with father (OR = 1.24; 95% CI = 1.00–1.54) clusters had higher odds of obesity. Conclusions : Women whose mothers were not in stable marriage relationships had higher odds of being overweight or obese in adulthood. The finding that even women raised in the context of stable cohabitation had higher odds of being overweight or obese is intriguing as these relationships are socially accepted in Sweden.